Eco-Geography of Feral Cotton: A Missing Piece in the Puzzle of Gene Flow Dynamics Among Members of Gossypium hirsutum Primary Gene Pool - Alavez, Valeria; Cuervo-Robayo, Ángela P.; Martínez-Meyer, Enrique; Wegier, Ana (Frontiers in Ecology and Evolution, 2021)
Mexico is the center of origin and genetic diversity of upland cotton (Gossypium hirsutum L.), the most important source of natural fiber in the world. Currently, wild and domesticated populations (including genetically modified [GM] varieties) occur in this country and gene flow among them has shaped the species’ genetic diversity and structure, setting a complex and challenging scenario for its conservation. Moreover, recent gene flow from GM cultivars to wild Mexican cotton populations has been reported since 2011. In situ conservation of G. hirsutum requires knowledge about the extent of its geographic distribution, both wild and domesticated, as well as the possible routes and mechanisms that contribute to gene flow between the members of the species wild-to-domesticated continuum (i.e., the primary gene pool). However, little is known about the distribution of feral populations that could facilitate gene flow by acting as bridges. In this study, we analyzed the potential distribution of feral cotton based on an ecological niche modeling approach and discussed its implications in the light of the distribution of wild and domesticated cotton. Then, we examined the processes that could be leading to the escape of seeds from the cultivated fields. Our results indicate that the climatic suitability of feral plants in the environmental and geographic space is broad and overlaps with areas of wild cotton habitat and crop fields, suggesting a region that could bridge cultivated cotton and its wild relatives by allowing gene flow between them. This study will provide information for management efforts focused on the conservation of wild populations, native landraces, and non-GM domesticated cotton at its center of origin and genetic diversity.